A Mechanism Leading to Changes in Copy Number Variations Affected by Transcriptional Level Might Be Involved in Evolution, Embryonic Development, Senescence, and Oncogenesis Mediated by Retrotransposons - Sui, Yunpeng; Peng, Shuanghong (Frontiers in Cell and Developmental Biology, 2021)
In recent years, more and more evidence has emerged showing that changes in copy number variations (CNVs) correlated with the transcriptional level can be found during evolution, embryonic development, and oncogenesis. However, the underlying mechanisms remain largely unknown. The success of the induced pluripotent stem cell suggests that genome changes could bring about transformations in protein expression and cell status; conversely, genome alterations generated during embryonic development and senescence might also be the result of genome changes. With rapid developments in science and technology, evidence of changes in the genome affected by transcriptional level has gradually been revealed, and a rational and concrete explanation is needed. Given the preference of the HIV-1 genome to insert into transposons of genes with high transcriptional levels, we propose a mechanism based on retrotransposons facilitated by specific pre-mRNA splicing style and homologous recombination (HR) to explain changes in CNVs in the genome. This mechanism is similar to that of the group II intron that originated much earlier. Under this proposed mechanism, CNVs on genome are dynamically and spontaneously extended in a manner that is positively correlated with transcriptional level or contract as the cell divides during evolution, embryonic development, senescence, and oncogenesis, propelling alterations in them. Besides, this mechanism explains several critical puzzles in these processes. From evidence collected to date, it can be deduced that the message contained in genome is not just three-dimensional but will become four-dimensional, carrying more genetic information.